2012
DOI: 10.1186/1471-2431-12-192
|View full text |Cite
|
Sign up to set email alerts
|

Parent-son decision-making about human papillomavirus vaccination: a qualitative analysis

Abstract: BackgroundLicensed for use in males in 2009, Human Papillomavirus (HPV) vaccination rates in adolescent males are extremely low. Literature on HPV vaccination focuses on females, adult males, or parents of adolescent males, without including adolescent males or the dynamics of the parent-son interaction that may influence vaccine decision-making. The purpose of this paper is to examine the decision-making process of parent-son dyads when deciding whether or not to get vaccinated against HPV.MethodsTwenty-one a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
76
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(83 citation statements)
references
References 26 publications
4
76
0
3
Order By: Relevance
“…These studies have found that public insurance status, Hispanic race, lower family income, having received flu vaccine, increased perceived vaccine effectiveness, peer acceptance and anticipated inaction regret, were associated with increased vaccine uptake or uptake intent in males (6)(7)(8)(9)(10).…”
Section: Most Published Research On Factors Associated With Hpv Vaccimentioning
confidence: 98%
“…These studies have found that public insurance status, Hispanic race, lower family income, having received flu vaccine, increased perceived vaccine effectiveness, peer acceptance and anticipated inaction regret, were associated with increased vaccine uptake or uptake intent in males (6)(7)(8)(9)(10).…”
Section: Most Published Research On Factors Associated With Hpv Vaccimentioning
confidence: 98%
“…4,[18][19][20]71,74,[76][77][78] However, the extent to which parents communicated about HPV vaccination beyond giving consent varied, with qualitative studies suggesting that parents from racial/ethnic minorities or with lower socioeconomic status were less likely to be engaged by providers and more likely than parents from more socially privileged backgrounds to defer to providers' advice. 19,71,73,74,77 Parents were also more likely to follow providers' advice without question when they received a strong, unambiguous recommendation.…”
Section: Communication Rolesmentioning
confidence: 99%
“…80 Studies suggested that parent-adolescent decisions were largely concordant and that most dyads ultimately reached agreement about the vaccination decision, but they sometimes looked to providers for guidance in the case of initial disagreement. 76,81 Interestingly, one qualitative study noted that adolescents' participation in medical dialog was often subtle and included non-verbal forms of communication such as nods, suggesting that adolescents' communication role could be easy to overlook. 76 …”
Section: Communication Rolesmentioning
confidence: 99%
See 2 more Smart Citations